2007
DOI: 10.1111/j.1399-3038.2006.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the compliance with once‐daily sublingual immunotherapy in children (EASY Project: Evaluation of A novel SLIT formulation during a Year)

Abstract: Compliance is a major determinant for allergy treatment, especially in children. Sublingual immunotherapy (SLIT) is self-managed at home, and no quantitative data on pediatric adherence are available. We studied the compliance in a large real-life setting. A simplified schedule of SLIT was used, consisting of a 10-day updosing phase followed by maintenance treatment in monodose containers to be taken daily (SLITOne). Italian specialists throughout Italy assessed the compliance in children who were newly prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 20 publications
3
41
0
1
Order By: Relevance
“…data are in agreement with several previously published studies of patients with PAR, which have reported the rates of around 70-80%[10,15,[17][18][19][20][21][22]. Another study has reported a higher compliance of approximately 97%[20].However, in that study, the patients counted the pills themselves and reported via a Variations caused by the method of compliance measurement were apparent in our study.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…data are in agreement with several previously published studies of patients with PAR, which have reported the rates of around 70-80%[10,15,[17][18][19][20][21][22]. Another study has reported a higher compliance of approximately 97%[20].However, in that study, the patients counted the pills themselves and reported via a Variations caused by the method of compliance measurement were apparent in our study.…”
supporting
confidence: 94%
“…The available data on the patient adherence to allergen-specific immunotherapy are often conflicting [11,12]. In particular, in allergic rhinitis, compliance rates for sublingual administration range between 70% and 97% [10,[13][14][15][16][17][18][19][20][21][22]. This wide variation might be explained by differences in the characteristics and methodology of the studies, such as the population profiles and the definition of compliance [23].…”
Section: Introductionmentioning
confidence: 91%
“…Costs are a common drawback for both AIT routes of administration [29,31,34,39,45,46,49,62]. An Italian study shows that costs are responsible for SLIT discontinuation over time.…”
Section: Causes Related To Treatmentmentioning
confidence: 98%
“…Concerning specific compliance and adherence studies, the available data indicate quite satisfactory results (74) The approach of evaluating the adherence by measuring the consume of allergen extracts was used in other 3 studies, which were facilitated by the fact that preparations in tablets or in liquid monodoses were employed (75,76,77). In the first ofthese the adherence value comprised between 75% and 97%, in the second 76.3% of the patients after 3 months and 74.8% of the patients after 6 months had compliance higher than 90%, in the third study on children a compliance rate higher than 75% was found in 85% of the children at the third month and in 84% of the children at the sixth month and the major cause of withdrawal (5.6% of the cases) was the cost of the treatment, while side effects accounted for 1.4% of stopping.…”
Section: Compliancementioning
confidence: 99%